Micro-masters of glioblastoma biology and therapy: increasingly recognized roles for microRNAs. Issue 5 (May 2014) - Floyd, Desiree; Purow, Benjamin
Abstract: MicroRNAs are small noncoding RNAs encoded in eukaryotic genomes that have been found to play critical roles in most biological processes, including cancer. This is true for glioblastoma, the most common and lethal primary brain tumor, for which microRNAs have been shown to strongly influence cell viability, stem cell characteristics, invasiveness, angiogenesis, metabolism, and immune evasion. Developing microRNAs as prognostic markers or as therapeutic agents is showing increasing promise and has potential to reach the clinic in the next several years. This succinct review summarizes current progress and future directions in this exciting and steadily expanding field.